2018
DOI: 10.2147/idr.s149590
|View full text |Cite
|
Sign up to set email alerts
|

Patient autonomy and disclosure of material information about hospital-acquired infections

Abstract: Hospital-acquired infections are nowadays a major health care problem worldwide. The morbidity and mortality associated with them are highest in intensive care units, but their effects are identifiable in virtually any medical department. Information about hospital-acquired infections, especially about their preventive measures, are rarely presented nowadays in a correct fashion to patients. This article aims to present, in a structured manner, the theoretical and practical aspects related to disclosure of hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 38 publications
(47 reference statements)
0
22
0
3
Order By: Relevance
“…The most of HAIs are urinary tract infections (UTIs), surgery-related infections, pneumonia, and primary sepsis [27], [28]. As previously mentioned, newborns enter to intensive care units (ICUs) are at high risk of developing nosocomial infections (NIs); due to their illness and exposure to invasive medical devices and the presence of multi-resistant microorganisms [28], [29], [30]. The nosocomial infections (NIs) in very low birth weight (VLBW) babies increase in 15% to 25% [31], [32], [30].…”
Section: Bacterial Infections In Nicumentioning
confidence: 99%
See 4 more Smart Citations
“…The most of HAIs are urinary tract infections (UTIs), surgery-related infections, pneumonia, and primary sepsis [27], [28]. As previously mentioned, newborns enter to intensive care units (ICUs) are at high risk of developing nosocomial infections (NIs); due to their illness and exposure to invasive medical devices and the presence of multi-resistant microorganisms [28], [29], [30]. The nosocomial infections (NIs) in very low birth weight (VLBW) babies increase in 15% to 25% [31], [32], [30].…”
Section: Bacterial Infections In Nicumentioning
confidence: 99%
“…As previously mentioned, newborns enter to intensive care units (ICUs) are at high risk of developing nosocomial infections (NIs); due to their illness and exposure to invasive medical devices and the presence of multi-resistant microorganisms [28], [29], [30]. The nosocomial infections (NIs) in very low birth weight (VLBW) babies increase in 15% to 25% [31], [32], [30]. Other statistics have found that neonatal infections cause about 1 million deaths every year globally.…”
Section: Bacterial Infections In Nicumentioning
confidence: 99%
See 3 more Smart Citations